Geographic and taxonomic trends of rising biological invasion costs - Haubrock, Phillip J; Cuthbert, Ross N; Hudgins, Emma J; Crystal-Ornelas, Robert; Kourantidou, Melina; Moodley, Desika; Liu, Chunlong; Turbelin, Anna J; Leroy, Boris; Courchamp, Franck (The Science of the total environment, 2022)
Invasive alien species (IAS) are a growing global ecological problem. Reports on the socio-economic impacts of biological invasions are accumulating, but our understanding of temporal trends across regions and taxa remains scarce. Accordingly, we investigated temporal trends in the economic cost of IAS and cost-reporting literature using the InvaCost database and meta-regression modelling approaches. Overall, we found that both the cost reporting literature and monetary costs increased significantly over time at the global scale, but costs increased faster than reports. Differences in global trends suggest that cost literature has accumulated most rapidly in North America and Oceania, while monetary costs have exhibited the steepest increase in Oceania, followed by Europe, Africa and North America. Moreover, the costs for certain taxonomic groups were more prominent than others and the distribution also differed spatially, reflecting a potential lack of generality in cost-causing taxa and disparate patterns of cost reporting. With regard to global trends within the Animalia and Plantae kingdoms, costs for flatworms, mammals, flowering and vascular plants significantly increased. Our results highlight significantly increasing research interest and monetary impacts of biological invasions globally, but uncover key regional differences driven by variability in reporting of costs across countries and taxa. Our findings also suggest that regions which previously had lower research effort (e.g., Africa) exhibit rapidly increasing costs, comparable to regions historically at the forefront of invasion research. While these increases may be driven by specific countries within regions, we illustrate that even after accounting for research effort (cost reporting), costs of biological invasions are rising.
Keywords: Plants; meta-analysis; North America; Severní Amerika; Evropa; Ecosystem; meta-regression; InvaCost; Time-series trends; zvířata; Europe; Invasive alien species; Socio-economic impact; zavlečené druhy; Animals; Introduced Species; Long term data; rostliny; ekosystém